M. Night Shyamalan : interviews - Shyamalan, M. Night; Gmelch, Adrian, 1993- (Jackson : University Press of Mississippi, 2023)
Two decades of interviews with the visionary filmmaker of such successful films as The Sixth Sense, Signs, and Unbreakable.
How to Master the Supernatural -- "The Only Thing That Matters to Me Is What I Think about My Own Films -- M. Night Shyamalan Interview: Split, Nonconformity, Creative Freedom -- Superheroes as a Disease of Cinema? M. Night Shyamalan Interviewed about Glass -- M. Night Shyamalan Reflects on the Evolution of His Career, His Filmmaking Philosophy, and That Old Ending -- Jury President M. Night Shyamalan: "The Berlinale Is a Mini Film School -- "Terrorized by This Light in Us -- Further Reading -- Index -- About the Editor
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 29, 2023).
JSTOR
Keywords: Shyamalan, M. Night; Shyamalan, M. Night; Motion picture producers and directors -- United States -- Interviews; Motion picture producers and directors -- India -- Interviews; Producteurs et réalisateurs de cinéma -- États-Unis -- Entretiens; Producteurs et réalisateurs de cinéma -- Inde -- Entretiens; PERFORMING ARTS / Individual Director; Motion picture producers and directors; India; United States; Electronic books; Electronic books; Interviews